Data "Airworthiness and No Fault Found - FRAM Analysis" - Lacey, Laura (Cranfield University, 2023)
The Functional Resonanace Analysis Method model (diagram) and Excel spreadsheet analysis completed within the PhD. The analyses shows how the impact of NFF can be monitored and reduced. It considers the aircrew, engineers, maintenance etc within an organization. The FRAM has been applied by following the guidance provided in this book. FRAM: The Functional Resonance Analysis Method: Modelling Complex Socio-technical Systems By Erik Hollnagel